Different perspectives in economic theory - Hartley-Ballestero, Rocío (2021)
The article is a synthesis of the contributions of some economic thinkers, in relation to how they structured a macroeconometric model. This work integrates authors who are they not usually analyzed together, which allows a syntax, which facilitates the comparison of their perspectives on economic theory or closing rules. It is a very difficult compendium to find in the abundant specialized literature, which also does not address the methodological specificities of each author, in relation to how they used the closure rules in their respective models. This void is what the document intends to correct, using a homogeneous mathematical structure, which makes it easier to visualize and understand clearly, how these thinkers closed their corresponding models. He realizes in the analysis, that it is possible to make combinations of various thoughts, which lead to a coherent result of the reality that you want to analyze. Subsequently, the schools of thought that represent them are they synthesized.